Computer and Information Science
DOI: 10.1007/978-3-540-79187-4_20
|View full text |Cite
|
Sign up to set email alerts
|

An Industrial Study Using UML Design Metrics for Web Applications

Abstract: Many web applications have evolved from simple HTML pages to complex applications that are difficult to maintain. In order to control the maintenance of web applications quantitative metrics and models for predicting web applications maintainability must be used. This paper introduces new design metrics for measuring the maintainability of web applications from class diagrams. The metrics are based on Web Application Extension (WAE) for UML and measure the design attributes of size, complexity, and coupling. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In order to control the maintenance cost of web applications, we have defined several design metrics for web applications as shown in Table 1. We also have conducted several empirical case to show the usefulness of the metrics [15,17,18,20,19,16]. Our main goal in this paper is to show how the WapMetrics tool can be used to compute UML design metrics for web applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to control the maintenance cost of web applications, we have defined several design metrics for web applications as shown in Table 1. We also have conducted several empirical case to show the usefulness of the metrics [15,17,18,20,19,16]. Our main goal in this paper is to show how the WapMetrics tool can be used to compute UML design metrics for web applications.…”
Section: Discussionmentioning
confidence: 99%
“…All the metrics are direct metrics except for WebControlCoupling, WebDataCoupling, and WebReusability which are indirect metrics. All these metrics were defined in the authors previous study [17], while the following (NC, NA, NM, NAssoc, NAgg) metrics were defined in the study carried by Genero [14] on class diagram metrics for object oriented applications. We have used the metrics in several studies: In [17] the pet store web application version 1.3.1 was used.…”
Section: Web Application Modeling Using the Unified Modeling Languagementioning
confidence: 99%
“…We decided to use UML design metrics since most of the studies use source code metrics for measuring maintainability despite the fact that many studies have shown that early metrics are much more useful [15,16]. For the authors previous research upon which this plan is based please refer to [17,18,19]. Modeling is a technique used to represent complex systems at different levels of abstraction, and helps in managing complexity.…”
Section: Related Workmentioning
confidence: 99%
“…The following metrics (NServerP, NClientP, NWebP, NFormP, NFormE, NLinkR, NSubmitR, NbuildsR, NForwardR, NIncludeR, NClientScriptsComp, NServerScriptsComp, WebControlCoupling, WebDataCoupling, WebReusability) were defined in the authors previous study [17]. The following (NC, NA, NM, NAssoc, NAgg) metrics were defined in the study carried by Genero [14] on class diagram metrics for object oriented applications.…”
Section: Independent Variablesmentioning
confidence: 99%